Konseling Seksual Terbukti Efektif dalam Meningkatkan Fungsi Seksual pada Pasien Gagal Ginjal Kronik di Kota Bekasi - Natalia Suraningsih; Diana Irawati; Dyah Untari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Chronic kidney disease in advanced stages requires hemodialysis. On the other hand, one of the complications of this disease is decreased sexual function in both men and women, so they need sexual counseling. The purpose of this study was to determine the effectiveness of BETTER model sexual counseling (raising topics about sexuality, explaining, telling, managing educational time, and recording) on the sexual function of patients with chronic kidney disease of reproductive age undergoing hemodialysis at dr. CAM Hospital, Bekasi. This study used a pretest and posttest with control group design, involving 42 respondents selected using purposive sampling techniques, which were then divided into treatment groups and control groups. The treatment group received sexual counseling using the BETTER model method in 6 stages, with a duration of 60 minutes per session. Data on sexual function in the pre- and post-intervention phases in both groups were collected using questionnaires filled out by the respondents. Differences in sexual function between before and after the intervention were analyzed using a paired sample t-test. The results of the analysis in the treatment group showed a p value = 0.000 for both men and women; which means there was a change in sexual function. Meanwhile, the p-value for the control group was 0.484 for men and 0.133 for women; which means that there was no change in sexual function. Furthermore, it was concluded that BETTER model sexual counseling is effective in improving sexual function in patients with chronic renal failure of reproductive age undergoing hemodialysis.Keywords: chronic renal failure; hemodialysis; sexual function; sexual counseling ABSTRAK Penyakit ginjal kronik pada stadium lanjut memerlukan hemodialisis. Di sisi lain, salah satu komplikasi dari penyakit ini adalah penurunan fungsi seksual baik pada laki-laki maupun perempuan, sehingga mereka membutuhkan konseling seksual. Tujuan penelitian ini adalah untuk mengetahui efektivitas konseling seksual model BETTER (mengangkat topik tentang seksualitas, menjelaskan, menceritakan, mengatur waktu mendidik, dan merekam) terhadap fungsi seksual pasien dengan ginjal kronik usia reproduktif yang menjalani hemodialisis di RSUD dr. CAM, Bekasi. Penelitian ini menggunakan desain pretest and posttest with control group, melibatkan 42 responden yang dipilih menggunakan teknik purposive sampling, yang selanjutnya dibagi menjadi kelompok perlakuan dan kelompok kontrol. Kelompok perlakuan mendapatkan konseling seksual menggunakan metode model BETTER dalam 6 tahap, dengan durasi 60 menit per sesi. Data tentang fungsi seksual pada fase sebelum dan sesudah intervensi pada kedua kelompok dikumpulkan menggunakan kuesioner yang diisi oleh responden. Perbedaan fungsi seksual antara sebelum dan sesudah intervensi dianalisis menggunakan paired sample t-test. Hasil analisis pada kelompok perlakuan menunjukkan nilai p = 0,000 baik untuk laki-laki mapupun perempuan; yang berarti ada perubahan fungsi seksual. Sementara itu, nilai p untuk kelompok kontrol adalah 0,484 untuk laki-laki dan 0,133 untuk perempuan; yang berarti bahwa tidak ada perubahan fungsi seksual. Selanjutnya diimpulkan bahwa konseling seksual model BETTER efektif untuk meningkatkan fungsi seksual pasien dengan gagal ginjal kronik pada usia reproduktif yang menjalani hemodialisis.Kata kunci: gagal ginjal kronik; hemodialisis; fungsi seksual; konseling seksual